Musical semiosis as a process of learning and growth - Ojala, Juha (Routledge, 2020)
More emphasis is given to signification in music, since that aspect provides the basis for the meanings that musics—as multifaceted phenomena—have in the lives of individual people, their societies, and cultures. This chapter provides a view of how musical semiosis—signification—is permeated with learning and growth. At the core of semiotics of learning is the process of inquiry, the interpretation of signs, and the subsequent adaptation to the hard facts through adjustment of habits of feeling, action, and thinking. Yet, in order to consider the semiotics of music and learning, the concept needs to be delineated within a Peircean framework. Growth is necessary for cognitive processes, where “concepts have function in reasoning and in acting that is independent of perception”. If, however, subjects have become semiotically empowered agents by developing mechanisms of semiosis at large, they are also, presumably, capable of developing mechanisms of signification in music, since musical semiosis is a subset of general semiosis.
Keywords: semiotiikka; musiikkisemiotiikka; musiikkifilosofia; oppiminen